Comparative evaluation of antibacterial efficacy different bioactive smart composites: An in vitro study - Pradnya Ramkrishna Chaudhari; N D Shashikiran; Sachin Gugawad; Namrata Gaonkar; Swapnil Taur; Savita Hadkar; Shreya Bapat (Wolters Kluwer Medknow Publications, 2021)
Background: Composites are the widely used restorative materials, and over the year, newer restorative composites have been introduced to eliminate the drawbacks of previous ones. The recent advance in restorative dentistry is bioactive restorative materials. However, bacterial plaque formation on these restorations is the primary reason for secondary caries. Aims and objectives: The purpose of this study was to do the comparative evaluation of bioactive restorative composites (Beautifil Flow Plus, Activa BioACTIVE, and Filtek Z250 XT as control) for their antibacterial efficacy under in vitro conditions. Materials and Method: Thirty material blocks were used for this evaluation. Antibacterial efficacy was checked against Streptococcus mutans and observed under confocal laser scanning microscopy. Results: The results showed that Activa BioACTIVE shows maximum number of dead bacteria on the material surface compared to other groups. Conclusion: It can be concluded as it has maximum antibacterial efficacy among tested materials.